Proposal of CPU-Free Environment Using PC in Your Pocket Technology - Fatin Athirah, Azalan; Muhamad Idaham, Umar Ong (American Scientific Publisher, 2018)
This product is compatible with all modern android devices that helps in turn your android smartphone into a complete laptop. This product help to overcome the small screen size problem and limited mobile interface when using smartphones. This product can provide a large screen, keyboard and multi touch track pad. Problem statement that should be overcome by develop this product are people must spend a lot amount of money to upgrade or buy a new laptop, utilizes smartphone resources and limited usability of an android smartphones because of smaller screen compared to a laptop. Objectives of this product are to design a solution that can help the user to reduce cost of buying a new laptop, to develop a product that can improve the usability of the smartphones and to verify whether the product can utilize smartphone resources. Methodology use in development of this product is Rapid Application Development (RAD) which is a software development methodology that uses minimal planning in favor of rapid prototyping. This product enables user to display all the applications inside the smartphones into the larger screen and using the smartphones operating system. The contribution of this research will enable the consumer to utilize their pocket PC resources efficiently.